Single-molecule insights into torsion and roadblocks in bacterial transcript elongation. Issue 4 (8th August 2021) - Qian, Jin; Xu, Wenxuan; Dunlap, David; Finzi, Laura
ABSTRACT: During transcription, RNA polymerase (RNAP) translocates along the helical template DNA while maintaining high transcriptional fidelity. However, all genomes are dynamically twisted, writhed, and decorated by bound proteins and motor enzymes. In prokaryotes, proteins bound to DNA, specifically or not, frequently compact DNA into conformations that may silence genes by obstructing RNAP. Collision of RNAPs with these architectural proteins, may result in RNAP stalling and/or displacement of the protein roadblock. It is important to understand how rapidly transcribing RNAPs operate under different levels of supercoiling or in the presence of roadblocks. Given the broad range of asynchronous dynamics exhibited by transcriptional complexes, single-molecule assays, such as atomic force microscopy, fluorescence detection, optical and magnetic tweezers, etc. are well suited for detecting and quantifying activity with adequate spatial and temporal resolution. Here, we summarize current understanding of the effects of torsion and roadblocks on prokaryotic transcription, with a focus on single-molecule assays that provide real-time detection and readout.